Nationwide guideline implementation: a qualitative study of barriers and facilitators from the perspective of guideline organizations - Andrea C. Thoonsen; Anika Gans; Toby T. Broeders; Ilse van Beusekom; Diana M. J. Delnoij; Martine C. de Bruijne; Hanneke Merten (BMC Health Services Research)
Abstract Background Although the number of Dutch guidelines is growing, their uptake and impact in clinical practice lag behind. Dutch guideline organizations, including guideline developers, governmental agencies, health insurers and other national organizations, play a crucial role in developing, authorizing and/or supporting the use of guidelines. They influence end users' awareness, accessibility, understanding, acceptability and applicability of guidelines. In this study, we explored the barriers and facilitators that representatives of guideline organizations perceive in nationwide guideline implementation. Methods In this qualitative study, we conducted semi-structured interviews with 35 representatives of 24 different guideline organizations. We employed framework analysis, using the updated Consolidated Framework for Implementation Research (CFIR), and thematic analysis to guide our data analysis and synthesis. Results We found 45 different implementation barriers and 35 implementation facilitators. We identified seven overarching themes of interrelated barriers and facilitators that extended across the stakeholders involved and domains within the updated CFIR. These included 1) healthcare demand and resource availability, 2) implementation knowledge and expertise, 3) guideline characteristics: representation, evidence base and design, 4) partnerships and collaboration, 5) characteristics of guideline implementation planning, execution and evaluation strategies, 6) characteristics of healthcare professionals: need, capability, opportunity and motivation, and 7) legal and regulatory compliance. Conclusions We obtained valuable insights into the complex dynamics of barriers and facilitators perceived by guideline organizations in nationwide guideline implementation. Our findings help explain why healthcare professionals and healthcare facilities may (not), slowly or inconsistently adhere to guideline recommendations in practice. The identified barriers and facilitators provide guidance for policymakers to re-evaluate and improve nationwide quality and guideline implementation policies, to eventually improve clinical practice and health outcomes for patients.